THE INTERPRETATION OF THE "WOMAN" CONCEPT IN CHINGIZ AITMATOV'S NOVELLA "JAMILA" - Qurbonova Kamola Abdurahmonovna (International Journal of Literature and Language Studies, 2026)
In this article, the concept of “woman” is analyzed through Chingiz Aitmatov’s novella “Jamila.” The analysis is based on examples taken from the novella “Jamila” and employs methods of definition and description.